Economic loss acute gastroenteritis on households in Malaysia and it associated factors - Jusoh, Nur Nabila (2020)
Background: Acute gastroenteritis (AGE) imposes significant health and economic burden in Malaysia. The economic burden affects not only healthcare providers but also households’ finances. A community survey on the household financial loss due to AGE is warranted since the majority of affected individuals did not seek formal treatment. Objective: To study the economic loss attributable to AGE among households in Malaysia by estimating; 1) the direct healthcare, 2) direct non-healthcare and 3) indirect costs and to determine associated factors for total households’ economic loss. Methodology: A cross-sectional study was conducted between December 2019 and March 2020, using a bilingual costing proforma which was distributed using a paid web-based survey (Survey Monkey) among individuals with self-reported AGE in Malaysia. Descriptive analysis and linear regression were applied. Results: Overall, the average total households’ economic loss due to a single episode of AGE regardless of their utilisation of healthcare services was RM406.37 (± SD 885.73) with direct cost RM147.23 (± SD 703.09) and indirect cost RM259.14 (± SD 379.92). The cost was the highest among those who obtained inpatient care, followed by outpatient care and the least was among those who did not seek treatment. We also observed that the indirect cost was higher than the total direct cost. The multiple linear regression analysis showed that the total household income (RM0.14; 95% CI: 0.01, 0.27; p=0.043) and type of facility (private vs government) (RM1842.05; 95% CI: 395.13, 3288.98; p=0.014) had a significant association with the total households’ economic loss. Background: Acute gastroenteritis (AGE) imposes significant health and economic burden in Malaysia. The economic burden affects not only healthcare providers but also households’ finances. A community survey on the household financial loss due to AGE is warranted since the majority of affected individuals did not seek formal treatment. Objective: To study the economic loss attributable to AGE among households in Malaysia by estimating; 1) the direct healthcare, 2) direct non-healthcare and 3) indirect costs and to determine associated factors for total households’ economic loss. Methodology: A cross-sectional study was conducted between December 2019 and March 2020, using a bilingual costing proforma which was distributed using a paid web-based survey (Survey Monkey) among individuals with self-reported AGE in Malaysia. Descriptive analysis and linear regression were applied. Results: Overall, the average total households’ economic loss due to a single episode of AGE regardless of their utilisation of healthcare services was RM406.37 (± SD 885.73) with direct cost RM147.23 (± SD 703.09) and indirect cost RM259.14 (± SD 379.92). The cost was the highest among those who obtained inpatient care, followed by outpatient care and the least was among those who did not seek treatment. We also observed that the indirect cost was higher than the total direct cost. The multiple linear regression analysis showed that the total household income (RM0.14; 95% CI: 0.01, 0.27; p=0.043) and type of facility (private vs government) (RM1842.05; 95% CI: 395.13, 3288.98; p=0.014) had a significant association with the total households’ economic loss.